Envejecimiento, proceso biológico y oportunidad de intervención preventiva o terapéutica - Jara L., Rafael (Revista Hospital Clínico Universidad de Chile, 2008)
Ageing is a complex biological proccess that has been explained trhough different theories. Each one of these theories has produced a great body of knowledge and nowdays it seems possible find means of intervention the ageing proccess and develop therapeutical strategies from them. In this paper these theories are revised and some intervention means are mentioned.